Recent trends in graphene supercapacitors: from large area to microsupercapacitors. Issue 5 (17th February 2021) - Velasco, Andres; Ryu, Yu Kyoung; Boscá, Alberto; Ladrón-de-Guevara, Antonio; Hunt, Elijah; Zuo, Jinghan; Pedrós, Jorge; Calle, Fernando; Martinez, Javier
Abstract : In this perspective, the recent trends in graphene supercapacitor research are shown, from the use of pseudocapacitor elements to enhance the performance of large-area electrodes, to its miniaturization driven by versatile fabrication techniques. Abstract : Supercapacitors are being increasingly used as energy storage systems. Graphene, with its huge specific surface area, superior mechanical flexibility and outstanding electrical properties, constitutes an ideal candidate for the next generation of wearable and portable devices with enhanced performance. Since Stoller described the first graphene supercapacitor in 2008, significant developments have been made during this last decade in the development of new graphene-based electrodes. In this way, the specific capacitance has been improved from 135 to 2585 F g −1 and the cyclability has been enhanced from a capacitance retention of just over 80% after 1000 cycles to almost 100% after 20 000 cycles. This review describes how 3-dimensional porous graphene electrodes have been improved recently, from using large area processing techniques to microsupercapacitors. Specifically, (a) the use of graphene foam to obtain large area electrodes, (b) the development of the direct laser writing technique for fast, one-step, and low-cost production of graphene-based supercapacitors, (c) their miniaturization in the form of integrated microsupercapacitors and (d) their functionalization with different pseudocapacitive and electric double-layer capacitor materials to obtain higher capacitance values will be the topics discussed in this perspective.